Hubungan Self – Compassion dengan Risiko Terjadinya Postpartum Depression pada Ibu Postpartum di Wilayah Kerja Puskesmas Jelbuk Jember - Dwi Putri Maharani (Fakultas Keperawatan, 2025)
Postpartum depression is a non-psychotic mood disorder that can occur in postpartum mothers. Psychological factors, including maternal role acceptance, contribute to postpartum depression. Effective acceptance of the mother role requires positive self-perception, which involves self – compassion. Objective: This study aims to analyze the relationship between self – compassion and the risk of postpartum depression in postpartum mothers in the work area of the Jelbuk Health Center, Jember. Method: This quantitative correlative study employed a cross – sectional design, sampling 44 postpartum mothers from the Jelbuk Health Center using total sampling. Results: The results of this study showed that 28 (63.6%) postpartum mothers were not at risk of experiencing postpartum depression, and 16 (36.4%) mothers were at risk of experiencing postpartum depression. Spearman correlation analysis revealed a significant negative correlation (p < 0.05, r = -0.714) between self-compassion and postpartum depression risk. Conclusion: Self-compassion plays an important role in mothers as an effort to reduce the risk of postpartum depression by implementing aspects of self – kindness, common humanity, and mindfulness. The study findings indicate a significant negative relationship between self-compassion and postpartum depression risk (r = -0.714), which means that the higher the level of self – compassion, the lower the risk of mothers experiencing postpartum depression
Reaploud Repository Hasyim April 2026
Keywords: Postpartum Depression; Self – Compassion; Postpartum Mother